Gestión de casos: adaptación para pacientes pluripatológicos y cuidadores en Colombia - Sandra Milena Hernandez-Zambrano; Sonia Patricia Carreño-Moreno; Ruth Alexandra Castiblanco-Montañez; Lorena Mesa-Melgarejo; Lorena Chaparro-Diaz; Ana Julia Carrillo-Algarra (Universidad Francisco de Paula Santander, 2021)
Objective: Identify the points of consensus of decision makers, professionals, and users, re-garding the fundamental aspects a Case Management Model should have in the Colombian context, to care for people with comorbidity and their family caregivers. Method: Descriptive study. Consensus decision-making among experts and convenience sampling. The Delphi method was applied in real time for two rounds. The analysis included arithmetic means to determine the most important and manageable proposals. Results: 25 experts participated in the first round and 23 in the second round. A greater consensus was obtained in: avail-ability of economic resources to guarantee sufficient infrastructure and human resources; qualification of human resources; potentiate the figure of the nurse in case management; implementation of comprehensive health care pathways; information systems that facilitates the transition and connection of the users; plans for high engagement of social actors to promote self-management. Conclusion: The adaptation of the Case Management Model in the Colombian insurance system, allowed the identification of substantial factors to implement it in the macro, meso and micro levels of the health care system, recognized by the actors as highly fragmented.